A recombinant topoisomerase I ELISA: screening for IgG, IgM and IgA anti-topo I autoantibodies in human sera. - Verheijen, R (1992)
An ELISA for the detection of anti-topoisomerase I autoantibodies in sera from patients with suspected or manifest rheumatic diseases is described. The antigen source used in this assay consists of a recombinant protein containing the last 695 C-terminal amino acid residues of human topoisomerase I (topo I). The sensitivity of the assay was 61%, while the specificity was more than 98%. Using this ELISA, 47 sera from scleroderma patients and immunopositive for anti-topo I antibodies, were screened for the presence of the isotypes IgG, IgA and IgM to topo I. Our finding that relatively high levels of IgA antibodies to topo I are present in most of the sera tested is consistent with the results of Hildebrandt et al. [1]. In addition, it is demonstrated that the IgG and IgA antibodies in a serum may recognize different epitope regions on the topo I polypeptide.